Impacts of Fertilization on Biologically Cycled P in Xylem Sap of Fagus sylvatica L. Revealed by Means of the Oxygen Isotope Ratio in Phosphate - Hauenstein, Simon; Nebel, Micha; Oelmann, Yvonne (Frontiers in Forests and Global Change, 2020)
Studies on the effect of high atmospheric N deposition report inconsistent results on forest productivity and N cycling which might be related to P availability in soil and subsequently affect tree P nutrition. We wanted to test the effects of (i) site i.e., a P-poor versus a P-rich site and of (ii) fertilization (N, P, N+P) on inorganic P (Pi) and organic P (Po) concentrations as well as on biologically cycled phosphate (inferred from the O isotope signature after adding an 18O-enriched label) in xylem sap. We measured Pi and Po concentrations and the O isotope signature in phosphate (δ18OPi) in xylem sap of beech (Fagus sylvatica L.) trees two and 14 days after addition of 18O-enriched water to the organic layer in a full factorial fertilization experiment (control, +N, +P, +NP) at two sites differing in P availability. Higher P concentrations in xylem sap at the P-rich than at the P-poor site originated from accelerated biological P cycling indicated by incorporation of 18O from the isotope label into phosphate in xylem sap shortly after labeling. At this site, δ18OW values of xylem sap after label application remained close to background δ18OW values of soil solution. We speculate that in contrast to P uptake, trees took up water from deeper (non 18O-labeled) soil layers. At the P-poor site, the 18O label was recovered both in xylem sap water and phosphate in xylem sap, the latter only after 14 days. These results imply that trees relied on the organic layer for P acquisition and water uptake. However, biological processes associated with an incorporation of 18O from the label were slower at the P-poor than at the P-rich site. P addition (P, NP) increased Pi concentrations in xylem sap at the P-rich site. Based on δ18OPi values in xylem sap, the additional P originated both from the fertilizer and from accelerated biological P cycling in soil. We conclude that P-poor sites likely suffer more from climate change in case of an increased frequency of droughts because as opposed to P-rich sites both water and nutrient uptake will be affected.